Amelioration of Alzheimer's disease pathology by mitophagy inducers identified via machine learning and a cross-species workflow - Xie, C.; Zhuang, X. X.; Niu, Z.; Ai, R.; Lautrup, S.; Zheng, S.; Jiang, Y.; Han, R.; Gupta, T. S.; Cao, S.; Lagartos-Donate, M. J.; Cai, C. Z.; et al. (Nat Biomed Eng, 2022)
A reduced removal of dysfunctional mitochondria is common to aging and age-related neurodegenerative pathologies such as Alzheimer's disease (AD). Strategies for treating such impaired mitophagy would benefit from the identification of mitophagy modulators. Here we report the combined use of unsupervised machine learning (involving vector representations of molecular structures, pharmacophore fingerprinting and conformer fingerprinting) and a cross-species approach for the screening and experimental validation of new mitophagy-inducing compounds. From a library of naturally occurring compounds, the workflow allowed us to identify 18 small molecules, and among them two potent mitophagy inducers (Kaempferol and Rhapontigenin). In nematode and rodent models of AD, we show that both mitophagy inducers increased the survival and functionality of glutamatergic and cholinergic neurons, abrogated amyloid-beta and tau pathologies, and improved the animals' memory. Our findings suggest the existence of a conserved mechanism of memory loss across the AD models, this mechanism being mediated by defective mitophagy. The computational-experimental screening and validation workflow might help uncover potent mitophagy modulators that stimulate neuronal health and brain homeostasis.
Xie, ChenglongZhuang, Xu-XuNiu, ZhangmingAi, RuixueLautrup, SofieZheng, ShuangjiaJiang, YinghuiHan, RuiyuGupta, Tanima SenCao, ShuqinLagartos-Donate, Maria JoseCai, Cui-ZanXie, Li-MingCaponio, DomenicaWang, Wen-WenSchmauck-Medina, TomasZhang, JianyingWang, He-LingLou, GuofengXiao, XiangluZheng, WenhuaPalikaras, KonstantinosYang, GuangCaldwell, Kim ACaldwell, Guy AShen, Han-MingNilsen, HildeLu, Jia-HongFang, Evandro Feng81600977/National Natural Science Foundation of China (National Science Foundation of China)000/China Scholarship Council (CSC)2021021/Ministry of Health and Care Services | Helse Sor-Ost RHF (Southern and Eastern Norway Regional Health Authority)262175/Norges Forskningsrad (Research Council of Norway)EnglandNat Biomed Eng. 2022 Jan 6. pii: 10.1038/s41551-021-00819-5. doi: 10.1038/s41551-021-00819-5.